2020
DOI: 10.3390/rs12030343
|View full text |Cite
|
Sign up to set email alerts
|

Tree Cover Estimation in Global Drylands from Space Using Deep Learning

Abstract: Accurate tree cover mapping is of paramount importance in many fields, from biodiversity conservation to carbon stock estimation, ecohydrology, erosion control, or Earth system modelling. Despite this importance, there is still uncertainty about global forest cover, particularly in drylands. Recently, the Food and Agriculture Organization of the United Nations (FAO) conducted a costly global assessment of dryland forest cover through the visual interpretation of orthoimages using the Collect Earth software, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 83 publications
(115 reference statements)
2
10
0
1
Order By: Relevance
“…With this method, we obtained a classification OA of 92.5%. This is a comparable result to the ones observed by different high-resolution classification studies done by Du et al [45] for crop area using Worldview-2 satellite data, De Alban et al [22] for mangrove forest cover and Guirado et al [46] for tree cover estimation, using various machine learning techniques. Furthermore, our study in some regions showed slightly higher accuracy compared to an earlier study done by Le Maire et al [23], using MODIS data.…”
Section: Discussionsupporting
confidence: 88%
“…With this method, we obtained a classification OA of 92.5%. This is a comparable result to the ones observed by different high-resolution classification studies done by Du et al [45] for crop area using Worldview-2 satellite data, De Alban et al [22] for mangrove forest cover and Guirado et al [46] for tree cover estimation, using various machine learning techniques. Furthermore, our study in some regions showed slightly higher accuracy compared to an earlier study done by Le Maire et al [23], using MODIS data.…”
Section: Discussionsupporting
confidence: 88%
“…We tested the ability of human analysts and a custom DNN to detect the invasive miconia plant in visible-wavelength UAS imagery collected over complex canopy forest and found that the DNN outperformed the human analysts. While similar results have been reported in other image classification studies [91,99], we are not aware of any prior studies involving rigorous time-controlled human trials for detecting invasive species in high-resolution UAS imagery. The significance of optical contrast and SCR as factors for human recall agrees with previous studies [100], and recent work has further associated poor accuracies with low SCR for both humans and DNNs [101,102].…”
Section: Discussionsupporting
confidence: 86%
“…Performing automatic monitoring of olive tree growth would be essential in these regions to effectively address these threats. Nowadays, the application of machine learning methods on very high spatial resolution satellite and aerial images opens the possibility of detecting isolated shrubs and trees at regional scale [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%